Fabrication and Electrical Discharge Machining of Al-SiC-Mg Composite with Mechanical Characterisation - Kula Bhusan Pradhan; Biswajit Nayak; Sudeep Kumar Singh (International Journal of Engineering and Management Research, 2018)
Composites are the materials obtained by combinations of different materials, with greater and better properties that are not present in the individual parent material. Due to its outstanding properties like light weight, corrosion resistance, higher strength and better thermal and electrical properties it is widely used. More than 40000 products of composite materials are used across the Globe. In this work Aluminium Metal Matrix Composite is formed with varying percentage of SiC and Mg. The electrical discharge machining (EDM) of the fabricated composite material has done to observe the material removal rate (MRR) and surface roughness along with different tests such as XRF, hardness test, tensile test and compression test. This paper represents the information that are observed after conducting various tests on composites casted by varying the percentage of Sic and Mg.From Various tests it is observed that with increase in percentage of SiC and Mg hardness, Young’s modulus and MRR increases.